2006
DOI: 10.1074/mcp.t600024-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Generation of High Density Protein Microarrays by Cell-free in Situ Expression of Unpurified PCR Products

Abstract: Due to the success of DNA microarrays and the growing numbers of available protein expression clones, protein microarrays have become more and more popular for the high throughput screening of protein interactions. However, the widespread applicability of protein microarrays is currently hampered by the large effort associated with their production. Apart from the requirement for a protein expression library, expression and purification of the proteins themselves and the lacking stability of many proteins rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
81
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(82 citation statements)
references
References 38 publications
(32 reference statements)
0
81
0
1
Order By: Relevance
“…However, the challenge associated with expressing thousands of full-length proteins and immobilizing them in a native state on a chip is daunting (5,6). In practice, the role of protein arrays has been limited, and the literature contains few examples of their successful use.…”
mentioning
confidence: 99%
“…However, the challenge associated with expressing thousands of full-length proteins and immobilizing them in a native state on a chip is daunting (5,6). In practice, the role of protein arrays has been limited, and the literature contains few examples of their successful use.…”
mentioning
confidence: 99%
“…The use of plasmids as the template is suboptimal as plasmid generation also requires long and tedious cloning and transformation steps. Angenendt et al have shown that PCR products can serve directly as templates for protein synthesis and protein array production, further streamlining the approach [11]. A second problem associated with the NAPPA method is that synthesis is not compartmentalized.…”
Section: In Vitro Protein Synthesismentioning
confidence: 99%
“…The binding of Hisx6-tagged green fl uorescence protein (GFP) and untagged GFP to Ni surface was compared by probing immobilized proteins with anti-GFP and anti-penta-His antibodies. Anti-GFP antibodies produced similar signals while anti-penta-His antibody signal was seen only in Hisx6-GFP, suggesting that unspecifi c binding to Ni slides rather than uniform attachment of Hisx6 tag to Ni may be responsible for protein binding (1). Other limitations of utilizing Ni-His affi nity in functional microarrays arise from the fact that Ni-His interaction can be disrupted by washing, prolonged storage or commonly used reagents including EDTA and DTT (57).…”
Section: Protein Immobilizationmentioning
confidence: 99%
“…Interestingly, the assumption that the binding of Hisx6-labeled proteins to Ni chips is dependent on His tag has been recently challenged (1). The binding of Hisx6-tagged green fl uorescence protein (GFP) and untagged GFP to Ni surface was compared by probing immobilized proteins with anti-GFP and anti-penta-His antibodies.…”
Section: Protein Immobilizationmentioning
confidence: 99%
See 1 more Smart Citation